Pengaruh Kepemimpinan, Budaya Organisasi dan Bimbingan Teknis terhadap Kinerja Pegawai (Studi Kasus pada Kantor Camat Peusangan Selatan Kabupaten Bireuen) - Ibrahim, Ibrahim; Faisal, S.; Yanna, Sri (Singkite Journal, 2024)
This study aims to try to analyze the impact of leadership, organizational culture and technical guidance on employee performance. The study was a survey with associative-quantitative methods. Analysis with statistical inference based on a structural model (path). Involving respondents from all employees at the Peusangan Selatan District Office, Bireuen Regency, totaling 40 people. The results of the study showed, 1) there was a significant influence of leadership, organizational culture, and technical guidance on employee performance, each strong category was 58.46%, 52.99% and 42.91%. 2) Also simultaneously leadership, organizational culture and technical guidance made a real contribution to improving employee performance at the District Office by 68.4%